Intertextualita v mluvených projevech (Úvahy o metodologii výzkumu a konceptuální soustavě) - Hoffmanová, Jana (Stylistyka, 2002)
The study concems the means of „reproducing" (or paraphrasing) the speech of others in the dialogue. The speech of others or ofthe participant himselfmay be „cited", but it is not literally a citation or reproduction, rather a transfomrntion of the original text. In a spoken dialogue, it is difficult to distinguish between direct speech, indirect speech, free direct speech and free indirect speech, as well as between the „reproduction" of speech actually given (whether by the participant or by others), and the „reproduction" of thoughts (the participants or others). Special attention is given the introductory sentences and connectives.